Evaluation of selectivity and bycatch mitigation measures using bioeconomic modelling. The cases of Madagascar and French Guiana shrimp fisheries - Chaboud, Christian; Vendeville, Philippe (Aquatic living resources (Montrouge), 2011)
Tropical shrimp fisheries are characterized by various interactions with their natural environment and with other fisheries. These latter interactions can be explained by the high quantity of bycatch taken by industrial trawler fleets, which has a significant impact on fish populations associated with shrimps and thus also on finfish fisheries. Bycatch also includes emblematic species, which are subject to strict conservation measures decided by the international community. It seems important to identify and assess the biological and economic consequences of different mitigation measures (increase of mesh size, turtle excluder devices and bycatch reducing devices). This communication is based on case studies undertaken on the Indian white prawn (Fenneropenaeus indicus) and speckled shrimp (Metapenaeus monoceros) fisheries in Madagascar and on the brown shrimp (Farfantepenaeus subtilis) and pink spotted shrimp (Farfantepenaeus brasiliensis) fishery in French Guiana. A review of the impacts of these fisheries on resources and ecosystems is made and some results of experiments on mitigation devices given. Finally, the results of simulations obtained using a multi-species, multi-fleet, age-structured bioeconomic model, including modifications of catchability and costs related to the adoption of these devices, is presented and discussed.